Stabilization mechanism and chemical demulsification of water-in-oil and oil-in-water emulsions in petroleum industry: A review. (15th February 2021) - Wang, Duo; Yang, Diling; Huang, Charley; Huang, Yueying; Yang, Dingzheng; Zhang, Hao; Liu, Qi; Tang, Tian; Gamal El-Din, Mohamed; Kemppi, Tom; Perdicakis, Basil; Zeng, Hongbo
Graphical abstract: Highlights: Stabilization mechanisms of W/O and O/W emulsions are distinctly different. Interface-active species and their multidirectional effects are discussed. Different types and influencing factors of EBs and REBs are reviewed. Demulsification mechanisms of EBs for W/O emulsions are introduced. Demulsification mechanisms of various REBs for O/W emulsions are discussed. Abstract: Emulsions frequently encountered in petroleum production, include water-in-oil (W/O) emulsions, oil-in-water (O/W) emulsions, and water-in-oil-in-water (W/O/W) emulsions, which considerably increase operation and production costs and cause technical challenges such as fouling and corrosion. Chemical treatment as a primary method has been extensively applied to destabilize the highly stable and complex emulsions. Demulsifiers play a vital role in demulsification efficiency of the chemical treatment, while developing effective and cost-efficient demulsifiers remains challenging due to complexity of the emulsions and poorly-understood demulsification mechanisms. This work systematically reviews the stabilization mechanisms of the complex emulsions, including the presence of interface-active species and their effects on the intermolecular and surface forces involved, properties of oil/water interface, and bulk properties of the emulsions. According to the different stabilization mechanisms of W/O emulsions and O/W emulsions, we subdivide demulsifiers into emulsion breakers (EBs) applied to demulsify W/O emulsions and reverse emulsion breakers (REBs) for O/W emulsions. The two types of demulsifiers are comprehensively reviewed and discussed, including types, influencing factors, demulsification mechanisms, and overdose effects. Our work provides useful insights into the fundamental stabilization and destabilization mechanisms of W/O emulsions and O/W emulsions and improves the understanding of efficient EBs and REBs and their applications in crude oil production and other related chemical and environmental engineering processes.